1981
DOI: 10.1073/pnas.78.2.936
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of hepatic glutathione formation by administration of L-2-oxothiazolidine-4-carboxylate, a 5-oxo-L-prolinase substrate.

Abstract: 5-Oxo-L-prolinase, the enzyme that catalyzes the conversion of 5-oxo-L-proline to L-glutamate coupled to the cleavage of ATP to ADP and Pi, also acts on L-2-oxothiazolidine-4-carboxylate (an analog of 5-oxoproline in which the 4-methylene moiety is replaced by sulfur) and ATP to yield cysteine and ADP. The enzyme, which exhibits an affinity for the analog similar to that for the natural substrate, is inhibited by the analog in vitro and in vivo. L-2-Oxothiazolidine-4-carboxylate thus serves as a ptent inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0
2

Year Published

1984
1984
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(66 citation statements)
references
References 17 publications
3
61
0
2
Order By: Relevance
“…Previous studies have demonstrated that OTC is more effective than N-acetylcysteine in replenishing intracellular GSH stores (Williamson and Meister, 1981;Mesina et al, 1989) and blocks airway hyperresponsiveness and inflammation in an asthmatic animal model (Lee et al, 2004c). Consistent with previous observations, administration of OTC decreases airway inflammation.…”
Section: Discussionsupporting
confidence: 78%
“…Previous studies have demonstrated that OTC is more effective than N-acetylcysteine in replenishing intracellular GSH stores (Williamson and Meister, 1981;Mesina et al, 1989) and blocks airway hyperresponsiveness and inflammation in an asthmatic animal model (Lee et al, 2004c). Consistent with previous observations, administration of OTC decreases airway inflammation.…”
Section: Discussionsupporting
confidence: 78%
“…specific inhibitor of glutathione synthesis, 42 or with OTC, 10 mg/day, which contributes to glutathione synthesis. 43,44 BSO treatment reduced MPM glutathione content by 22%, whereas OTC treatment increased cellular glutathione content by 26%, compared with control non-supplemented E 0 mice ( Figure 3A). In contrast, MPM lipid peroxide levels increased by 300% in BSO-treated E 0 mice, compared with control E 0 mice ( Figure 3B).…”
Section: Resultsmentioning
confidence: 99%
“…N ¼ number of subjects in the study; F ¼ female; M ¼ male; Rxo6week ¼ on antipsychotic medication within 6 weeks of death (only typical neuroleptics). Table 1 Continued N-acetylcysteine is used to target cystine-glutamate antiporters because it is a prodrug for cyst(e)ine (Williamson and Meister, 1981;Meister, 1985;Pileblad and Magnusson, 1992). However, cysteine can also be transported by the sodium-dependent glutamate transporter EAAC1 (Aoyama et al, 2006).…”
Section: N-acetylcysteine Attenuates Pcp-evoked Performance Deficits mentioning
confidence: 99%